PENGARUH KUALITAS PEYANANAN KESEHATAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RSUD PURI HUSADA TEMBILAHAN ÔÇô INDRAGIRI HILIR - jurnalmap map; Ervis Pratika; Hadi Susanto; Esa Wahyu Endarti (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to describe the effect of the quality of health services on inpatient satisfaction at RSUD Puri Husada Tembilahan. This type of research is explanatory research (explanatory research). Data collection techniques using a questionnaire (questionnaire), Observation (Observation) and Documentation. Determination of the sample of this study uses the incidental sampling method that is taking patients who need services at RSUD Puri Husada Tembilahan. The results of the study using a partial test (t test) found that the independent variables, namely responsiveness, assurance, physical evidence, attention and reliability partially significant effect on the dependent variable, namely patient satisfaction in RSUD Puri Husada Tembilahan, Indragiri Hilir Regency. From the F test results obtained an F count of 19,029 and a significance level of 0,000. Because the significance level is 0,000 <0.05, the hypothesis is accepted. This means that responsiveness, guarantees, physical evidence, attention and reliability together have a significant effect on patient satisfaction at RSUD Puri Husada Tembilahan, Indragiri Hilir Regency.Keywords: satisfaction, responsiveness, guarantee, physical evidence, attention, reliability.